Reflex antenatal DNA screening for Down syndrome. (14th August 2015) - Wald, Nicholas J.; Huttly, Wayne J.; Bestwick, Jonathan P.; Aquilina, Joe; Peregrine, Elisabeth
Abstract : What's already known about this topic? Modelling has shown the efficacy of reflex DNA screening for Down syndrome. The DNA test can be triggered (i.e. reflexed) by a risk estimate from a conventional test such as the Combined test using a plasma sample collected at the same time as the conventional test sample. The method linked to the Combined test has an estimated 91% Down syndrome detection rate and a false‐positive rate of 0.025% if 10% of women are 'reflexed' to a DNA test. The method also detects trisomy 18 and trisomy 13 pregnancies. What does this study add? The reflex DNA screening method has been introduced for the first time into routine antenatal care. The method was introduced without difficulty with 127 women (10.5%) having a reflex DNA test. Five DNA tests were positive – three Down syndrome and two trisomy 13 – with no false positives. The method avoids women experiencing unnecessary anxiety by avoiding the need to issue a Combined test result and recall women for a second test.